Management of Motion and Anatomical Variations in Charged Particle Therapy: Past, Present, and Into the Future - Pakela, Julia M.; Knopf, Antje; Dong, Lei; Rucinski, Antoni; Zou, Wei (Frontiers in Oncology, 2022)
The major aim of radiation therapy is to provide curative or palliative treatment to cancerous malignancies while minimizing damage to healthy tissues. Charged particle radiotherapy utilizing carbon ions or protons is uniquely suited for this task due to its ability to achieve highly conformal dose distributions around the tumor volume. For these treatment modalities, uncertainties in the localization of patient anatomy due to inter- and intra-fractional motion present a heightened risk of undesired dose delivery. A diverse range of mitigation strategies have been developed and clinically implemented to monitor and correct for patient motion, but much work remains. This review provides an overview of current clinical practices for motion management in charged particle therapy as well as progress to date on emerging technologies.